Penelope Fitzgerald : a life - Lee, Hermione (Alfred A. Knopf, 2014)
English writer "Fitzgerald, born into an accomplished intellectual family, the granddaughter of two bishops, led a life marked by dramatic twists of fate, moving from a bishop's palace to a sinking houseboat to a last, late blaze of renown. We see Fitzgerald's very English childhood in the village of Hampstead; her Oxford years, when she was known as the 'blonde bombshell'; her impoverished adulthood as a struggling wife, mother, and schoolteacher, raising a family in difficult circumstances; and the long-delayed start to her literary career"--Amazon.com.